Influence of an Acute Exacerbation During Pulmonary Rehabilitation in Patients With Chronic Obstructive Pulmonary Disease Awaiting Lung Transplantation. Issue 4 (July 2021) - Gloeckl, Rainer; Jarosch, Inga; Leitl, Daniela; Schneeberger, Tessa; Nell, Christoph; Langer, Daniel; Koczulla, Andreas R.; Kenn, Klaus
Abstract : Patients with chronic obstructive pulmonary disease awaiting lung transplantation can achieve clinically relevant improvements in exercise performance and quality of life following pulmonary rehabilitation, even if they develop an acute exacerbation during rehabilitation. Abstract : Purpose: Pulmonary rehabilitation (PR) has been shown to be an effective intervention in patients with very severe chronic obstructive pulmonary disease (COPD) awaiting lung transplantation (LTx). The objective of this study was to characterize the prevalence of acute exacerbations (AEs) during PR and their impact on the outcomes of pre-LTx PR. Methods: In this retrospective analysis, 559 patients with COPD awaiting LTx who were referred to a 4-wk inpatient PR program were evaluated. A total of 114 patients (20%) acquired an AE during PR and continued in an adapted fashion. Pulmonary function testing, 6-min walk test (6MWT), and a health-related quality-of-life questionnaire (SF-36) were administered on admission and on discharge of PR. Results: Following PR, both groups, patients with and without AE, increased their 6MWT significantly ( P < .001) to a clinically relevant amount (58 ± 72 and 52 ± 64 m, respectively). The sum scores of the SF-36 also improved significantly without any between-group differences. No observed changes were different between the two groups. No relevant predictors for PR outcomes could be detected by logistic regression. Conclusions: Our data show that patients with end-stage COPD listed for LTx can achieve clinically relevant improvements in functional exercise capacity and quality of life even if they develop an AE during PR.